Combinatorial anticancer effects of curcumin and sorafenib towards thyroid cancer cells via PI3K/Akt and ERK pathways. Issue 16 (17th August 2016) - Zhang, Junjia; Yu, Jichun; Xie, Rong; Chen, Wanzhi; Lv, Yunxia
Abstract: The objective of this study was to examine the in vitro combinatorial anticancer effects of curcumin and sorafenib towards thyroid cancer cells FTC133 using a MTT cytotoxicity assay, and to test whether the mechanism involves induction of apoptosis. The present results demonstrated that curcumin at 15–25 μM dose-dependently suppressed the proliferation of FTC133. Combined treatment (curcumin (25 μM) and sorafenib (2 μM)) resulted in a reduction in cell colony formation and significantly decreased the invasion and migration of FTC133 cells compared with that treated with individual drugs. Western blot showed that the levels of p-ERK and p-Akt proteins were significantly reduced ( p < 0.01) in the medicine-treated FTC133 cells. The curcumin was found to dose-dependently inhibit the apoptosis of FTC133 cells possibly via PI3K/Akt and ERK pathways. There is a synergetic antitumour effect between curcumin and sorafenib. Graphical abstract: